Internet dan Ruang Publik Virtual, Sebuah Refleksi atas Teori Ruang Publik Habermas - NASRULLAH, RULLI (Universitas Muhammadiyah Yogyakarta, 2012)
Public sphere which is popularized by Habermas is a historical review of the critical discussions in response to the political realities which happened in the 18th century society. The emergence of the internet as new media gives broader transformation, both practically and theoretically, on how public sphere occurs in the virtual world. Characteristics of the internet as media, users who access it and the information which is distributed in virtual public sphere basically become a vital point to see what the real character of public sphere in the virtual world is. Keywords: public sphere, new media, network, information